Voltage-Gated Potassium Channels as Regulators of Cell Death - Bachmann, Magdalena; Li, Weiwei; Edwards, Michael J.; Ahmad, Syed A.; Patel, Sameer; Szabo, Ildiko; Gulbins, Erich (Frontiers in Cell and Developmental Biology, 2020)
Ion channels allow the flux of specific ions across biological membranes, thereby determining ion homeostasis within the cells. Voltage-gated potassium-selective ion channels crucially contribute to the setting of the plasma membrane potential, to volume regulation and to the physiologically relevant modulation of intracellular potassium concentration. In turn, these factors affect cell cycle progression, proliferation and apoptosis. The present review summarizes our current knowledge about the involvement of various voltage-gated channels of the Kv family in the above processes and discusses the possibility of their pharmacological targeting in the context of cancer with special emphasis on Kv1.1, Kv1.3, Kv1.5, Kv2.1, Kv10.1 and Kv11.1.